(untitled) (Imaginations: Journal of Cross-Cultural Image Studies, 2020)
Breast cancer, if it advances, is life threatening. It is also widespread. My life was changed when I was diagnosed with breast cancer. There was much that I did not expect, including a hegemonic culture of “breast conservation.” I opted to “go flat” after bilateral mastectomy, resisting reconstruction plastic surgery. A politics of choice—like that demanded for reproductive rights—has yet to find similar resonance in the world of breast cancer treatment. This article considers reconstruction hegemony and the emerging movement to advance the choice to be, in words coined by a pioneering Facebook group, Flat and Fabulous.